Complementary and alternative medicine interventions for perioperative symptoms: A comparative effectiveness study. (June 2019) - Schiff, Elad; Attias, Samuel; Matter, Ibrahim; Sroka, Gideon; Nae, Bluma; Arnon, Zahi; Samuels, Noah; Grinberg, Ofra; Ben-Arye, Eran
Abstract: Introduction: Perioperative symptoms such as pain, nausea and anxiety are often inadequately treated. We conducted a pragmatic trial to evaluate the impact of Complementary and Alternative Medicine (CAM) treatments on these symptoms, within the framework of a general surgery department that integrates CAM. Methods: Patients ≥ 18 years referred to CAM treatments by surgical medical staff were allocated to standard of care with CAM treatment (CAM group) or without, according to patient preference and practitioner availability. CAM treatments included Acupuncture, Reflexology, or Guided Imagery. The primary outcome variable was the change from baseline in symptom severity, measured by Visual Analogue Scale (VAS). Patients and practitioners were asked to report any adverse effects associated with CAM treatments. Results: A total of 1127 patients were enrolled, 916 undergoing 1214 CAM treatments and 211 controls. Socio-demographic characteristics were similar in both groups. Patients in the CAM group had more severe baseline symptoms. Symptom reduction was greater in the CAM group compared with controls, with a mean reduction in pain of −2.17 ± 2.4 vs −0.29 ± 2 ( P  < 0.0001); nausea −1.2 ± 2.42 vs −0.3 ± 1.94 ( P  < 0.0001); and anxiety −2.23 ± 2.76 vs −0.03 ± 2.54 ( P  < 0.0001). Acupuncture was more effective for nausea control. No significant adverse events were reported with any of the CAM therapies. Conclusion: CAM treatments provide additional relief to Standard Of Care (SOC) for perioperative symptoms. Larger randomized control trial studies with longer follow-ups are needed to confirm these benefits. The study is registered with clinical trials.gov at (NCT01733771).